The dynamics of supply and demand chain of English-medium schools in Bangladesh. (20th October 2017) - Mousumi, Manjuma Akhtar; Kusakabe, Tatsuya
ABSTRACT: This research concerns English-medium schools (EMSs), which are emerging as a popular new educational sector in Bangladesh. Because these schools have gained immense popularity, we seek to identify how these schools respond to parental demand and retain their clientele. In addition to English language demand, our findings reveal a symmetrical relationship between the supply of EMSs and parental demand. EMSs' strategic business planning and market forces, which emphasise deficiencies in the supply chain of Bangla-medium schools (BMSs), have motivated parents to send their children to EMSs. We conclude that although English-medium education is a high-cost educational alternative, its introduction as a new educational initiative is based on its transnational quality and acceptance.